Why they stayed: a study of the working lives of long serving teachers in inner city schools - McIntyre, Joanna (2010)
This study explores ways in which the experiences of long-serving teachers within three inner city schools can improve our understanding of factors that influence teachers to remain in the profession. The research is situated within a socio-political climate where there are concerns about teacher attrition in general and where the issue of teacher retention is perceived to be particularly acute in challenging schools. The thesis challenges the prevailing discourses surrounding inner city schools and the teachers who work in them by turning to the voices of experienced teachers and exploring their reasons for remaining in these schools.